Application Of The Yassarna Method In Learning The Yellow Islamic Classic Book Of The Islamic Boarding School - Hasan Al Banna; Abuddin Nata; Khalimi Khalimi; M. Suparta; Abdul Ghofur (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This research is based on the background of the low level of ability to read the yellow scriptures caused by the inaccurate choice of learning methods, this research is important to do in order to test the effectiveness of the level of application of the yassarna method in learning to read the yellow scriptures quickly and correctly. The purpose of this study is to describe and explain the content of the yassarna method with the relationship of behavioristic theory and the success and failure of the yassarna method. This research is a qualitative research at the exploratory level of analysis. Primary data sources are observation and direct interviews with the organizers of the Yassarna method, such as students, pesantren administrators, ustadz and students. Secondary data in the form of yassarna method book modules, as well as those related to the yassarna method. The result of this study is the yassarna method as a yellow scriptures learning of Abdul Hamid Sholeh Jombang pesantren provides a solution in the process of learning the kitab kuning quickly and well. One of the successes of learning the yassarna method is being active in learning, enthusiasm in singing the verses of each table column. The relationship between behavioristic theory and the yassarna method is interrelated, because the behavioristic method can facilitate educators and students in the learning process. Keywords: Yellow Scriptures, Pesantren, Yassarna Method